Synthesis, Enzyme Assays and Molecular Docking Studies of Fluorina ted Bioisosteres of Santacruzamate A as Potential HDAC Tracers - Ahamed, Muneer; Vermeulen, Koen; Schnekenburger, Michael; Roman Moltzau, Lise; Olav Levy, Finn; Marton, Janos; Froeyen, Mathy; Erlend Olberg, Dag; Diederich, Marc; Bormans, Guy (Letters in Drug Design & Discovery, 2017)
Background: Histone deacetylases (HDACs) emerged as important epigenetic regulators of gene expression. Method: In order to identify potential positron emission tomography (PET) tracers for imaging HDACs, we evaluated in vitro and in cellulo activities of some compounds that were reported as potent HDAC2-selective inhibitors. We observed marked differences between reported activity values and the values obtained in our assays for some of the compounds. To understand the structural basis of the activity of some of these inhibitors, we also performed molecular docking studies to understand their interaction patterns and binding modes with HDAC2. Results and Conclusion: We observed the low affinity compounds 4, 6 and 7 did not showed equal number of key π-π interactions and hydrogen bonding when compared to high affinity compounds, and could be the possible reason for poor inhibition as reflected in in vitro assays. These preliminary experimental and computational results will help to interpret the HDAC affinity values of these key compounds with caution.
Keywords: PET tracers